1992
DOI: 10.1111/j.1600-0404.1992.tb05111.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings in lupus ataxia

Abstract: We present a 47-year-old white woman who had a definitive diagnosis of systemic lupus erythematosus (SLE), and developed cerebellar ataxia of sudden onset. MR imaging showed changes characteristics of cerebellar infarct. Due to the absence of vascular risk factors and to the previous diagnosis of SLE, we postulate that the cerebellar infarct is related to SLE. We are not aware of previous descriptions of the MRI findings in lupus ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Previous studies suggested that cerebral infarction and vasculopathy are possible pathogenic mechanisms involved in cerebellar ataxia in SLE patients. [4][5][6] In our patients, cerebral ischemia was less likely seen in patients #1 and #2 because of the absence of typical ischemic MRI abnormalities on initial and follow-up MRI. Although patient #3 had an ischemic cerebellar lesion, her MRI also showed slight contrast enhancement, suggesting blood-brain barrier rupture secondary to an underlying vasculitis.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous studies suggested that cerebral infarction and vasculopathy are possible pathogenic mechanisms involved in cerebellar ataxia in SLE patients. [4][5][6] In our patients, cerebral ischemia was less likely seen in patients #1 and #2 because of the absence of typical ischemic MRI abnormalities on initial and follow-up MRI. Although patient #3 had an ischemic cerebellar lesion, her MRI also showed slight contrast enhancement, suggesting blood-brain barrier rupture secondary to an underlying vasculitis.…”
Section: Discussionmentioning
confidence: 61%
“…Focal CNS manifestations secondary to cerebellar involvement has rarely been described in SLE. [2][3][4][5][6][7][8][9][10][11][12] The sudden onset of nystagmus and ataxia suggests the presence of cerebellar dysfunctions that may occur as an isolated presentation, associated with brainstem or more widespread CNS manifestations. [7][8][9] We report three SLE patients who presented in our clinic with acute cerebellar ataxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 136 138 , 141 145 , 148 , 149 There was a single patient who had normal imaging studies, 140 and a single patient with T2 hyperintensity affecting the cerebellum. 146 Interestingly, there was 1 patient who had additional features of a limbic encephalopathy associated with an ataxia. 139 This patient presented with confusion and MRI showing FLAIR-hyperintense signals which affected the right medial temporal lobe, and also extended into the ipsilateral limbic pathways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Manto et al (1996) reported a pancerebellar syndrome of subacute progression in an SLE patient, and al‐Arfaj and Naddaf (1995) described a 40‐year‐old SLE female who presented with truncal ataxia and intention tremor. Lancman et al (1992) found bilateral cerebellar ischemic lesions on magnetic resonance imaging in a lupus patient with lateralization of gait and ataxia, and Tuchman et al (1983) reported cerebellar atrophy on neuroimaging in a patient that exhibited lupus ataxia. The actual incidence of cerebellar involvement in SLE is unknown.…”
Section: Introductionmentioning
confidence: 99%